Understanding criminal justice : sociological perspectives - Smith, Philip (Philip Daniel), 1964- (SAGE, 2005)
Providing an overview of the sociological approaches to law and criminal justice, this book focuses on how law and the criminal justice system inevitably affect one another, and the ways in which both are intimately connected with wider social forces.